(3WHbGJ GdTGaYjI GdcHQis - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO ajg JQLeI CHj GdaJM GdeUjUi GdGPQbi Ke GdOeTbi GdehdhO SfI(B448 s
(3BNQgG (B:s
(3HGddg jG UHM dGJRQfG aGdUHM MQH dbhe dhW BNQ GdeLdO GdKGdK ef WHbGJ GHf GdSHci s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs